APARTHEID’S LOST ATTACHMENTS (1): ON PSYCHOANALYTIC READING PRACTICE - Hook, Derek (PINS-Psychology in Society, 2025)
This paper, the first of two focussed on the topic of libidinal attachments between white children and black domestic workers in narratives contributed to the Apartheid Archive Project (AAP), offers a series of methodological insights derived from a Lacanian type of psychoanalytic reading practice. A Lacanian reading practice is one which emphasizes the importance of symbolic juxtaposition, of recombining different facets of texts, and of attempting to locate what I term the “absent mediator” implied by tacit conjunctions and associations within texts. In this paper I focus particularly on a puzzling aspect shared by a series of contributions to the AAP, namely the role of animals in the narratives of white participants, which appear to emerge precisely when the question of a loving relation for a black person is posed. I argue that this narrative device is an attempt to make sense of a prospective relationship, particularly when such a relationship is effectively prohibited by the prevailing rules of interaction. In response to pressing questions of inter-racial loss and love, and in respect of an ambiguous inter-racial relationship, recourse to an animal provides a fantasmatic “solution”, a model of how to manage a relationship that otherwise difficult to understand.